Unpacking access to Northern Ontario’s sexual assault evidence kits: Qualitative insights into barriers to comprehensive rural emergency sexual assault care - Timmermans, Sydney; Murphy-Oikonen, Jodie; Rice, Kathleen (Canadian Journal of Emergency Nursing / Journal canadien des infirmières d’urgence, 2026)
Background: Sexual assault evidence kits (SAEKs) are used to gather forensic evidence from survivors following sexual assault. This evidence collection coincides with comprehensive post-assault care and referrals to follow-up services. Many hospitals lack staff trained in SAEK use and sexual assault care, especially in rural areas. This study aimed to explore the barriers SAEK use in Northwestern Ontario.Methods: Nine semi-structured interviews were conducted with healthcare providers to assess challenges facing access to sexual assault care in rural and Northwestern Ontario. Data were analyzed using thematic analysis.Results: Three main themes were developed: 1) lack of training; 2) legal implications of the kit; 3) resource constraints. These themes invite discussion about the future of sexual assault care in rural emergency centers, specifically where it pertains to trauma informed care and forensic training, distance to care centers, hospital staffing and the medicolegal role of clinicians.Conclusion: Sexual assault trauma hinders many survivors from seeking care, especially when care has been inadequate in the past. This research provides insights into rural health inequities in Northern and rural Canada, and thus lends insight into the gaps that exist within the juncture of health and justice systems.